Evaluation of the impact of concomitant fibromyalgia on TNF alpha blockers' effectiveness in axial spondyloarthritis: results of a prospective, multicentre study. Issue 4 (28th November 2017) - Moltó, Anna; Etcheto, Adrien; Gossec, Laure; Boudersa, Nadia; Claudepierre, Pascal; Roux, Nicolas; Lemeunier, Lucie; Martin, Antoine; Sparsa, Lartitia; Coquerelle, Pascal; Soubrier, Martin; Perrot, Serge; et al.
Abstract : Objective: To describe the prevalence of fibromyalgia (FM) in an axial spondyloarthritis (axSpA) population and to confirm that concomitant FM had a negative impact on tumour necrosis factor blockers' (TNFb) response. Design: Prospective observational study with two visits 3 months apart. Patients: Adult patients with AxSpa initiating a TNFb. Study groups: FM was defined by the Fibromyalgia Rapid Screening Tool (FiRST) at baseline and also by a sustained positive FiRST (both visits) and by a fulfilment of the 1990 American College of Rheumatology criteria for FM. Statistical analysis: Prevalence of FM; evaluation of the impact of a concomitant FM on TNFb response (Bath Ankylosing Spondylitis Disease Activity Index (BASDAI 50) as primary endpoint), adjusted by factors known to have an impact on TNFb response. Results: Among the 508 patients included in the main analysis, 192 (37.8%) were screened at baseline as FM. Percentage of success after 12 weeks of treatment was lower in the FM group for most of the effectiveness endpoints (eg, BASDAI 50: 45.3% vs 54.1% in the FM/not FM groups according to the FiRST), except for the C reactive protein change endpoints which were not different across groups. Conclusion: This study confirms that FM coexists in patients with axSpA and that its presence seems to have a negative impact on TNFb response, which seems more related to the self-reported instruments used in its evaluation, rather than a different treatment effect of the molecule in this subgroup of patients.